Small-scale Fermentation of Cocoa Beans and on-Process Monitoring - Ariza Budi Tunjung-Sari; Hendy Firmanto; Teguh Wahyudi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Cocoa bean fermentation is a critical step in the formation of chocolate aroma precursors. Small-scale fermentation is needed to accommodate fermentation practice during low season and fruit scarcity. The study was conducted to address the minimum amount of wet cocoa beans required for a successful fermentation. In the trials, wet cocoa beans at different quantities, i.e. 1, 2.5, 5, 7.5, 10, 15, and 40 kg, were incubated in separate wooden boxes for 4 days (96 hours) and turned once after 48 hours. Temperature and pH of the pulp and beans were measured every 6 hours. Dry beans were visually inspected to determine the number of grayish and purple cotyledons indicating unfermented beans. In general, smaller scale fermentations, i.e. 1 to 15 kg, resulted in similar profiles with that of standard mini-box fermentation (40 kg) in terms of temperature, pulp pH and bean pH. The 40 kg fermentation resulted in the lowest percentage of purple beans with no grayish beans, meanwhile smaller scale fermentations showed higher number of unfermented beans. The logarithmic regression indicates that as much as 1.4 kg beans producing unfermented beans of less than 20% which meets the criteria of grade 3 based on the Indonesian National Standard for cocoa bean (SNI 2323:2008/Amd1:2010). Data analysis shows that temperature below 35°C for 42 hours was associated with higher percentage of grayish and purple beans. It is concluded that cocoa bean fermentation can be carried out at least at 5 kg scale, and temperature at 42 hours could be a parameter for process monitoring.